Advanced Colonoscopy Principles and Techniques Beyond Simple Polypectomy - Sonoda, Toyooki (Springer New York : Imprint: Springer, 2014)
This is a state-of-the-art book for those looking to advance their colonoscopic techniques beyond simple polypectomy. Chapters introduce methods of removing polyps that were not previously amenable to simple colonoscopic snare polypectomy. These include endoscopic mucosal resection (EMR), endoscopic submucosal dissection (ESD), and combined endoscopic and laparoscopic polypectomy (CELS). Advanced techniques such as intestinal stenting and closure of perforations are extensively covered. There is a detailed description of necessary tools and skills to accomplish these difficult tasks. As many readers will never have seen these complex procedures before, photographs and video clips accompany this text. The authors provide tips, tricks, and describe pitfalls that will help the reader incorporate these new techniques into their practice. Advanced Colonoscopy: Polypectomy and Beyond will be of great value to any surgeon or gastroenterologist currently performing colonoscopy and interested in advanced techniques. Supplementary video files are available for this book and can be accessed at http://www.springerimages.com/videos/978-1-4939-1583-5.